2022
DOI: 10.1093/femsec/fiac126
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of antifungal Acinetobacter bacteria isolated from the skin of the frogs Agalychnis callidryas and Craugastor fitzingeri

Abstract: Chytridiomycosis, a lethal fungal disease caused by Batrachochytrium dendrobatidis (Bd), is responsible for population declines and extinctions of amphibians worldwide. However, not all amphibian species are equally susceptible to the disease; some species persist in Bd enzootic regions with no population reductions. Recently, it has been shown that the amphibian skin microbiome plays a crucial role in the defense against Bd. Numerous bacterial isolates with the capacity to inhibit the growth of Batrachochytri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Genomic analysis of bacteria isolated from amphibian skin revealed the presence of genes linked to biosynthesis of various metabolites that could be linked to host protection against Bd and host-microbiome interactions [93,94,116]. Specifically, genes linked to AF traits have been linked to the biosynthesis of chitinolytic enzymes [22], and secondary metabolites such as ribosomal and non-ribosomal peptides (RiPP and NRPS), aryl-polyenes, polyketides, or bacteriocins [58,93,94].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic analysis of bacteria isolated from amphibian skin revealed the presence of genes linked to biosynthesis of various metabolites that could be linked to host protection against Bd and host-microbiome interactions [93,94,116]. Specifically, genes linked to AF traits have been linked to the biosynthesis of chitinolytic enzymes [22], and secondary metabolites such as ribosomal and non-ribosomal peptides (RiPP and NRPS), aryl-polyenes, polyketides, or bacteriocins [58,93,94].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate if genes linked to potential antifungal functions differed across seasons, elevations/sites and Bd infection status, a PERMANOVA test was used comparing abundances of genes linked to bacterial communication and competition traits (BCC: biofilm formation, quorum sensing and secretion systems) and potential antifungal functions (AF: secondary metabolite and chitinolytic enzyme biosynthesis). Selection of these gene categories was based on published literature suggesting that these functions may contribute to host protection against Bd [22,40,53,58,93,94].…”
Section: Gene Enrichment Analysis Of General Functions and Potential ...mentioning
confidence: 99%
“…Antifungal activity assay for the selected bacteria against B. cinerea Bacteria were previously identified by Rebollar et al (2019). The bacteria C26G and C32I were recently described as new species of the Acinetobacter genus (Cevallos et al, 2022), while C23F was identified at the family level as Enterobacteraceae through 16S rRNA sequencing (Rebollar et al, 2018). All bacteria isolates were initially screened for their antifungal activity against the pathogen B. cinerea by the direct confrontation assay.…”
Section: Methodsmentioning
confidence: 99%
“…This clade currently includes 14 species with correct names and five provisional taxa with not yet defined nomenclatural status (Table S1, ) [1]. In addition, several taxonomically unique strains belonging to the clade were reported [4–6]. The haemolytic clade consists of several subclades, which markedly differ from each other in phenotypic and genomic features.…”
Section: Introductionmentioning
confidence: 99%
“…1) [1]. In addition, several taxonomically unique strains belonging to the clade were reported [4][5][6]. The haemolytic clade consists of several subclades, which markedly differ from each other in phenotypic and genomic features.…”
Section: Introductionmentioning
confidence: 99%